The Palaeolithic settlement of Lefkas. Archaeological evidence in a palaeogeographic context - Galanidou, Nena; Iliopoulos, Giorgos; Papoulia, Christina (Journal of Greek Archaeology, 2016)
The chain of islands emerging from the Ionian Sea constitutes the western part of the active Hellenic Arc and is separated from the European landmass by the shaping forces of eustasy and tectonism. As part of the Ionian Margin, the islands share the same geological and climate regimes with their counterpart, the coastal zone of the west Greek mainland extending from Epirus to the Peloponnese. The Ionian setting consists of limestone geology and karst, rocks containing abundant cherts, high tectonic activity, tsunamis, and high rainfall rates. The pioneering work conducted by A. Sordinas on Corfu, Zakynthos and other islands in the 1960s, later by Cubuk on Kefalonia, and in the 1990s by A. Dousougli and C. Zachos on Lefkas, established the earliest component of Ionian prehistory and laid the foundations for further fieldwork with an explicit Palaeolithic focus. Surface surveys exploring the diachronic history of individual islands or the coastal zone of west Greece have added new points to the Palaeolithic map. Today, early Ionian prehistory is an independent research objective, going hand-in-hand with a shift of interest to early island and coastal archaeology. It is pursued through two interconnected lines of investigation: systematic fieldwork to enlarge the archaeological sample and explore the variation of hominin settlement in time and space, and re-appraisal of published material to fine-tune the archaeology, compare it, and place it in a palaeogeographic context.